Big bear hug - Oldland, Nicholas (Toronto : Kids Can Press, 2009)
A bear who loves to hug everything meets a human who is about to chop down a tree, and the bear must make a decision on how to save his forest.
Keywords: Hugging; Bears; Hugging; Picture books for children; Ours; Etreinte; Livres d'images pour enfants; Bears